Role of Nitric Oxide Carried by Hemoglobin in Cardiovascular Physiology: Developments on a Three-Gas Respiratory Cycle - Premont, Richard T; Reynolds, James D; Zhang, Rongli; Stamler, Jonathan S (Circulation research, 2020)
A continuous supply of oxygen is essential for the survival of multicellular organisms. The understanding of how this supply is regulated in the microvasculature has evolved from viewing erythrocytes (red blood cells [RBCs]) as passive carriers of oxygen to recognizing the complex interplay between Hb (hemoglobin) and oxygen, carbon dioxide, and nitric oxide-the three-gas respiratory cycle-that insures adequate oxygen and nutrient delivery to meet local metabolic demand. In this context, it is blood flow and not blood oxygen content that is the main driver of tissue oxygenation by RBCs. Herein, we review the lines of experimentation that led to this understanding of RBC function; from the foundational understanding of allosteric regulation of oxygen binding in Hb in the stereochemical model of Perutz, to blood flow autoregulation (hypoxic vasodilation governing oxygen delivery) observed by Guyton, to current understanding that centers on S-nitrosylation of Hb (ie, S-nitrosohemoglobin; SNO-Hb) as a purveyor of oxygen-dependent vasodilatory activity. Notably, hypoxic vasodilation is recapitulated by native S-nitrosothiol (SNO)-replete RBCs and by SNO-Hb itself, whereby SNO is released from Hb and RBCs during deoxygenation, in proportion to the degree of Hb deoxygenation, to regulate vessels directly. In addition, we discuss how dysregulation of this system through genetic mutation in Hb or through disease is a common factor in oxygenation pathologies resulting from microcirculatory impairment, including sickle cell disease, ischemic heart disease, and heart failure. We then conclude by identifying potential therapeutic interventions to correct deficits in RBC-mediated vasodilation to improve oxygen delivery-steps toward effective microvasculature-targeted therapies. To the extent that diseases of the heart, lungs, and blood are associated with impaired tissue oxygenation, the development of new therapies based on the three-gas respiratory system have the potential to improve the well-being of millions of patients.